Transformasi Pendidikan Islam di Era AI: Reorientasi Tujuan Belajar dari Kecerdasan Digital menuju Kecerdasan Spiritual - Yolanda Dwintarisma Andrini; Eka Sri Ruminingsih; Samsiyah Nuril Hidayah; Ahsan Hakim (Education Reserach Center, 2025)
This study seeks to develop a holistic framework for transforming Islamic Religious Education (PAI) by reorienting learning objectives, positioning Spiritual Intelligence (SI) as the ultimate goal (ghayah) and Digital Intelligence (DI) as an instrumental means (wasilah). Using a qualitative library research approach, the study systematically reviews primary and secondary sources from 2020–2025 and analyzes them through descriptive-analytical and content analysis methods. The findings show that DI enhances administrative efficiency, learning personalization, and access to Islamic knowledge, yet it has epistemological limitations, as it is non-empathetic, lacks a spiritual dimension, and cannot replace scholars in ijtihad or the transmission of tacit knowledge. Therefore, SI, grounded in Imam Al-Ghazali’s concept of tarbiyah al-qalb, serves as the axiological foundation for forming the insan kamil and akhlak karimah, while ethically regulating AI use through the framework of Maqasid al-Shari’ah, particularly Hifz al-Din and Hifz al-Aql. Pedagogically, this necessitates an integrative, contextual, and future-oriented PAI curriculum supported by spiritually based project-based learning, ethical digital media, Islamic digital literacy, and the strengthened role of educators as murabbi and value transformers.